An Arkansas Folklore Sourcebook - Clements, William M., 1945-; McNeil, W. K., 1940-2005 (Book collections on Project MUSE., 1992)
Arkansas's rich folklore tradition is treated in this collection of eight essays covering the history of folklore research in the state, traditional songs and music, "tall tales," folk architecture, traditional foods and their preparation, superstitions and beliefs, and festivals and celebrations. Includes extensive bibliographies of reference works, and audio and video recordings.